PPP IN RUSSIA. GENERAL STATUS AND IMPLEMENTATION - V. Laktionov (Вестник Северо-Кавказского федерального университета)
Analysis of such a process as PPP is necessary at this time, since it could help solve the problems of the Russian economy associated with various crisis manifestations. For effective functioning of public-private partnership, it is advisable to analyze the General state of PPP in the country. It is also necessary to go deeper into the process of implementing the PPP itself, as a project of the state and private parties. The article discusses the branches of the Russian economy that use the PPP mechanism. As a result of the research, we will get a conclusion about the socio-economic vector chosen by the state, which industries are priority for it and business, and what procedure follows the implementation.